Development and characterization of cactus–dextrin– recombinant human epidermal growth factor based silk scaffold for wound dressing applications. (April 2014) - Sukumar, N; Ramachandran, T; Lakshmikantha, CB
Silk fibroin (SF), a naturally occurring protein polymer, has several unique properties such as biocompatibility, biodegradability, minimal inflammatory reaction, and endowed with excellent mechanical properties and process ability. The existing scaffolds used in medical industry lack the degradation and/or slow in healing practice, so clinically there is a need for the development of efficient and reliable biomaterial scaffolds for wound healing. Silk fibroin has shown greater potential for tissue engineering applications. This work is focused on designing biomaterial with silk as raw material and wound healing effect of SF scaffolds were also tested. The silk blended scaffolds were prepared by using SF as a vehicle with dextrin, other healing agent of cactus and epidermal growth factor (rhEGF) are used as the drug releasing model. Scanning electronic microscope (SEM) was used to observe the morphology of prepared scaffolds for process versatility and the highly specific surface area. The structure was studied by Fourier transform infrared. The SF was treated at different concentrations of cactus and rhEGF, to investigate the growth inhibition effect of bacterial growth. The SF scaffolds show favorable stability by their structural integrity, morphology, mechanical properties, and powerful antibacterial efficacy up to 100% to Escherichia coli and Staphylococcus epidermidis significantly intended to provide improved environments for the zone of incubation when compared with normal scaffolds without rhEGF. Therefore, the results give the evidence for the application of SF blended scaffolds in the treatment of wound.